Non-Playable Character (NPC) based on Behaviour Tree for Enhanced Immersive Experience in the Serious Game "Warik's Adventure" - Siswoko, Tandicha Marchelputra; Haryanto, Hanny; Hastuti, Khafiizh; Kadiasti, Ristia (Journal of Applied Informatics and Computing, 2023)
Video games, or digital games, have transcended their traditional role of mere entertainment and are now being leveraged for more serious purposes, such as education and cultural preservation. Serious games offer the advantage of presenting content in an interactive and enjoyable manner. A crucial element in gameplay for creating interactivity and a pleasurable experience is the non-playable character (NPC). In serious games, replayability is pivotal for optimizing the comprehension of learning content, with the gameplay experience being a key factor influencing replayability. While games are known for their entertaining aspects, immersion design in serious games often falls short, resulting in a subpar experience. The NPC design in this study is grounded in appreciative learning, emphasizing positive outcomes such as possibilities, peak successes, exploration, and future optimism. The reward activity is structured across four levels: Discovery, Dream, Design, and Destiny. Behaviour Tree is employed to govern NPC behavior throughout all four stages. To evaluate the effectiveness of the immersive design, the Game Experience Questionnaire (GEQ) is employed, measuring three primary components"”sensory, imaginative, and challenge-based immersion. The GEQ result indicates a score of 3.2, showcasing a slight improvement from the previous version's score of 3.07. This research contributes to the enhancement of serious game design by focusing on NPC behavior and immersive experiences, ultimately fostering more effective and engaging learning environments.